MANAGEMENT OF ECONOMIC AND FINANCIAL STRATEGY INDUSTRIAL CORPORATION - K. B. Dobrova (Модернизация, инновация, развитие, 2016)
Issues related to creation of tools making it possible to efficiently control financial and economic production capability of industrial corporations making part of Russian military-industrial complex are discussed on example of an aviation enterprise. A system of balanced indicators is proposed to be used to develop corporation’s adaptive management strategies.